Questioning of Authentication and Epistemology in Tafsir al-Jilani - Irwan Masduqi (Balai Penelitian dan Pengembangan Agama Semarang, 2012)
In this research, the author critically analyzes a biography of Shaikh ‘Abd al-Qadir al-Jilani containing sacred myths. The analyst of sacred myth about ‘Abd al-Qadir al-Jilani is based on the approach of applied anthropology to distinguish between the myths that have positive and negative values for Muslim society. This research then analyzes the authenticity of Tafsir al-Jilani and the epistemology of his inter- pretation. ‘Abd al-Qadir al-Jilani is the founder of Qadiriyah. Qadiriyah doctrines has been widely accepted by traditional Muslim groups in Muslim world, so that the study of Tafsir al-Jilani is very meaningful for the followers of Qadiriyah in particu- lar and the lovers of Quranic studies in general to increase their knowledge about the teachings of ‘Abd al-Qadir al-Jilani.